Novel gelatin particle agglutination test for serodiagnosis of leprosy in the field. - Izumi, S (1990)
We developed a novel gelatin particle agglutination test (MLPA) for the serodiagnosis of leprosy; this test is especially useful for clinical practice and epidemiological surveys of leprosy in countries in which the disease is endemic. The antigen used in the test is the chemically synthesized trisaccharide moiety of Mycobacterium leprae-specific phenolic glycolipid I. MLPA is a simple and easy technique having sensitivity and specificity comparable to those of the conventional indirect enzyme-linked immunosorbent assay. The new technique was found to be useful for monitoring of chemotherapy and predictive diagnosis of high-risk individuals in contact with persons with leprosy and may be useful for the prediction of relapse. We are now preparing to supply a quality-controlled ready-to-use MLPA kit for leprosy control in countries in which leprosy is endemic.